2021
DOI: 10.1016/bs.ctdb.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the molecular mechanisms of axon guidance receptor regulation and signaling

Abstract: As the nervous system develops, newly differentiated neurons need to extend their axons toward their synaptic targets to form functional neural circuits. During this highly dynamic process of axon pathfinding, guidance receptors expressed at the tips of motile axons interact with soluble guidance cues or membrane tethered molecules present in the environment to be either attracted toward or repelled away from the source of these cues. As competing cues are often present at the same location and during the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 165 publications
(193 reference statements)
0
46
0
Order By: Relevance
“…This pathway and these terms include processes involved in neuron morphogenesis and neuron communication, thus the DETs in these processes could be important for translating the pituitary molecular stress response. By further dissecting the Reactome pathway ''Nervous system development'', we found that most DETs (30/ 31) could be mapped to the pathway ''Axon Guidance'', which describes the process by which neurons send out axons to reach their synaptic target (Zang et al, 2021). As shown in the heatmap, the majority of the upregulated DETs in this pathway code for ribosomal proteins (Figure 2B).…”
Section: Social Stress-induced Genes Are Involved In Neuron Morphogen...mentioning
confidence: 97%
“…This pathway and these terms include processes involved in neuron morphogenesis and neuron communication, thus the DETs in these processes could be important for translating the pituitary molecular stress response. By further dissecting the Reactome pathway ''Nervous system development'', we found that most DETs (30/ 31) could be mapped to the pathway ''Axon Guidance'', which describes the process by which neurons send out axons to reach their synaptic target (Zang et al, 2021). As shown in the heatmap, the majority of the upregulated DETs in this pathway code for ribosomal proteins (Figure 2B).…”
Section: Social Stress-induced Genes Are Involved In Neuron Morphogen...mentioning
confidence: 97%
“…During the last years, our understanding of the molecular mechanisms and proteins involved in the cytoskeletal transduction of axon guidance signaling has greatly progressed. While the list of upstream guidance cues and receptor families has not significantly grown, novel combinatorial mechanisms involved in signal transduction and cytoskeleton-regulatory proteins recipient of guidance information are continuously emerging ( Stoeckli, 2018 ; Zang et al, 2021 ). Among the latter, Microtubule-Associated Proteins (MAPs) represent a significant group.…”
Section: Future Directionsmentioning
confidence: 99%
“…During pathfinding GCs are simultaneously exposed to various signaling proteins and the final guidance decision relies on the spatial-temporal repertoire of guidance receptors expressed at the surface and the computation of their downstream signaling pathways. In addition, neuron-intrinsic molecular mechanisms including response-modulating co-receptors, receptor-receptor interactions, receptor clustering and oligomerization, proteolytic processing of receptors, or the trafficking of signaling receptors-carrying endosomes, contribute to the diversification of axonal responses to a same guidance cue ( Dudanova and Klein, 2013 ; Pasterkamp and Burk, 2021 ; Zang et al, 2021 ). These intracellular pathways ultimately converge on proteins managing the cytoskeleton remodeling in the axon and GC.…”
Section: Introductionmentioning
confidence: 99%
“…Consequent to neuronal maturation, this event, occurring all over the nervous system, regulates refinement of projections and is strongly supported by environmental factors. SEMAs are well-known players in axonal pathfinding [ 72 ], and not surprisingly also mediate their pruning.…”
Section: Axon Pruningmentioning
confidence: 99%